PARACETAMOL, MIGRAINE, AND MEDICATION OVERUSE HEADACHE (MOH) - Hanik Hidayati; Anung Kustriyani (Journal of Pain, Headache and Vertigo, 2020)
Paracetamol is a nonopioid synthesized p-aminophenol derivative that used as an antipyretic and an analgesic. Paracetamol is an over the counter medicine. 15.6% of migraine patients took paracetamol for headache relief. In migraine, paracetamol is used long term. This triggers paracetamol to cause Medication Overuse Headache (MOH). Animal studies associated paracetamol induced MOH based on pathophysiology migrenes. There three mechanism underline MOH include effect to korteks cerebral, effect to system trigeminal nociception, and effect to central modulating systems.